Teaching Islamic ethics and ethical training: benefiting from emotional and spiritual intelligence - Abdullah, Fatimah (Centre for Promoting Ideas, USA, 2012)
The development of good character in Islam is mostly a process of dealing with one’s emotions. It helps to build and support good emotions like mercy, love, generosity and courage and to fight and suppress negative emotions such as jealousy, anger, selfishness and cowardice. Character building would therefore, have much to do with patience and perseverance in controlling emotions leading to negative aspects and reinforcement of emotions leading to positive ethics. Manipulation of emotions leading to good ethics would also lead one to have a spiritually and psychologically healthy life. Modern research tells us that in management and industry, those who reinforce themselves with spiritual motivation and who are emotionally intelligent tend to attain a greater competitive edge over others who are not so inclined. The main aim of this research is to investigate the new area in modern psychology namely, emotional and spiritual intelligence to try to discover whether the new psychological approach and findings of positively studying human emotions can be of help in Islamic ethical training; this is of value because the development of good character in Islam is mostly a process of dealing with one’s emotions and with the emotions of others.